2019
DOI: 10.1007/s00404-019-05261-2
|View full text |Cite
|
Sign up to set email alerts
|

The PLART study: incidence of preterm labor and adverse pregnancy outcomes after assisted reproductive techniques—a retrospective cohort study

Abstract: Key message Even though assisted reproductive techniques represent one of the greatest achievements in modern medicine, the risk of preterm birth related to these pregnancies is about twice as high. This must be highlighted and further investigated to optimize the management of both mothers and newborns. Purpose The purpose of this study was to compare adverse pregnancy outcomes after assisted reproductive techniques (ART) and spontaneous conceptions, focusing on the incidence of preterm births (PTB) and disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Four studies were excluded due to the presence of overlapping cases [ 39 , 40 , 41 , 42 ]. Forty-eight studies that comprised 34,603,164 pregnancies and 59,241 pregnancies with endometriosis met the inclusion criteria for the descriptive analysis [ 26 , 27 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ,…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were excluded due to the presence of overlapping cases [ 39 , 40 , 41 , 42 ]. Forty-eight studies that comprised 34,603,164 pregnancies and 59,241 pregnancies with endometriosis met the inclusion criteria for the descriptive analysis [ 26 , 27 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ,…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that newborns conceived through the ART procedures were associated with an increased incidence of preterm delivery compared to those conceived spontaneously regardless of the type of ART procedure ( 2 4 ). According to previous studies, several possible factors such as embryo culture medium, in vitro culture to blastocyst stage, as well as embryo cryopreservation, might be related to PTB in couples treating with ART.…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort studies have compared the perinatal outcomes between singleton births using ART and singleton births from spontaneous conception, with adjustment for relevant confounders. 27,28 A meta-analysis that included 8044 singleton births assisted by either in vitro fertilization or intracytoplasmic sperm injection and 53 633 singleton births by spontaneous conception found that the risk of preterm birth was significantly increased in ART-conceived singleton births. 18 A cohort study in Finland reported that medically assisted reproduction, including ART and non-ART fertility drugs, was associated with an elevated risk of preterm birth outcomes.…”
Section: Discussionmentioning
confidence: 99%